2011
DOI: 10.1021/om1011648
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of Novel Luminescent Di-, Tri-, and Tetranuclear Copper Triazole Complexes

Abstract: A number of novel luminescent di-, tri-, and tetranuclear copper complexes have been synthesized in good yields using a modular ligand system based on triazole-phosphines. This kind of ligand is easily accessible through an improved one-pot synthesis that permits the facile introduction of various alkyl or aromatic substituents at the 1-, 4-, or 5-position of the triazole ring. X-ray crystallography revealed three different types of complexes: neutral di- and tetranuclear structures with C i symmetry, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 51 publications
2
56
0
2
Order By: Relevance
“…[19b] To prevent such behavior, bridging and chelating ligands may be employed. However, while many N-P ligands are known, [27] so far none of them gave planar, White-type complexes [Cu 2 X 2 (N-P) 2 ]. Instead, other structural motifs are often found.…”
Section: Historic Development Of Multinuclear Cu I Complexes With N Amentioning
confidence: 99%
“…[19b] To prevent such behavior, bridging and chelating ligands may be employed. However, while many N-P ligands are known, [27] so far none of them gave planar, White-type complexes [Cu 2 X 2 (N-P) 2 ]. Instead, other structural motifs are often found.…”
Section: Historic Development Of Multinuclear Cu I Complexes With N Amentioning
confidence: 99%
“…[4,5] Therefore, we chose to react equimolar quantities of ligand 3a and CuI as the metal source in dichloromethane (Scheme 4). Our group recently showed that copper complexes with triazolyl-phosphane ligands have interesting photoluminescence properties.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, phosphanebased molecules are ligands of choice in many different organometallic-catalyzed processes. [5] At this stage, our interest laid in the synthesis and study of similar structures that were additionally chiral, and this would possibly allow the formation of enantiopure metal complexes. [1] Following the reliable procedure of Sharpless for the synthesis of triazoles, [2] Zhang reported the first synthesis of the ClickPhos family of ligands [3] (1, Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The details of the theoretical calculations are described in the ESI. † Despite the diverse range of functionals and basis sets used for copper complexes in literature that oen provide good results, [50][51][52][53] the functional sensitivity of TD-DFT, especially for CT systems, 54 requires their careful screening in the luminescence studies. Geometry optimization.…”
Section: Computational Study Of Cu(i) Complexesmentioning
confidence: 99%